Significant increases in Donghong kiwifruit yield by a novel umbrella-shaped trellis system and identification of associated molecular mechanisms - Deng, Honghong; Li, Yao; Pang, Changqing; Zhang, Kun; Tian, Xinbo; Wang, Tong; Liang, Yan; He, Zunzhen; Lang, Yuxuan; Fang, Jinbao; Lin, Lijin; Wang, Jin; et al. (Frontiers in Plant Science, 2023)
China is the largest kiwifruit producer in the world, accounting for more than half of the total. However, in terms of yield per unit area, China is much lower than the global average and lags behind that of other countries. Yield improvement is of critical importance for the current kiwifruit industry in China. In this study, an improved overhead pergolas trellis (OPT) system, namely, the umbrella-shaped trellis (UST) system, was developed for Donghong kiwifruit, which is now the second most popular and widely cultivated red-fleshed kiwifruit in China. Surprisingly, the estimated yield on the UST system was more than two times higher than that with a traditional OPT, while the external fruit quality was maintained and the internal fruit quality was improved. One of the mechanisms contributing to the yield improvement was the significant promotion of the vegetative growth of canes at 6 ~ 10 mm in diameter by the UST system. The upper canopy of the UST treatment served as a natural shading condition for the lower fruiting canopy and thus had positive effects on the accumulation of chlorophylls and total carotenoids in the fruiting canopy. The most productive zones on the fruiting canes (6 ~ 10 mm in diameter) contained significantly higher (P < 0.05) levels of zeatin riboside (ZR) and auxin (IAA) and ratios of ZR/gibberellin (GA), ZR/abscisic acid (ABA), and ABA/GA. A relatively high carbon/nitrogen ratio may promote the flower bud differentiation process of Donghong kiwifruit. The outcomes of this study provide a scientific basis for manifold increase in production of kiwifruit and contribute to the sustainability of the kiwifruit industry.